Interactionsbetween of Orius sp. (Heteroptera: Anthocoridae) and Amblyseius (Typhlodromips) Swirskii (Athias-Henriot) (Acari: Phytoseiidae) for biological control of Thirps palmi karny (Thysanoptera: Thripidae) on muskmelon - Thi Thuy, Nguyen; Van Dai, Nguyen; Thi Phuong Thao, Nguyen (Vietnam Journal of Biotechnology, 2020)
In this study, we examined biological control Thirps palmi Karny of a predatory mite Amblyseius (Typhlodromips) swirskii (AthiasHenriot), the anthocorid bug Orius sp. and combination of Amblyseius swirskii and Orius sp. The experiments in laboratory condition showed that combination of these two species have the ability to prey consumtion is higher than using only predator (Orius sp. or Amblyseius swirskii). The fecundity of Orius sp. in the absence of Amblyseius swirskii (the total number of eggs/ females = 45.5 ± 2.25 eggs, the oviposition period = 16.49 ± 0.5 days) were higher than in the presence of Amblyseius swirskii (the total number of eggs/ females = 35.6 ± 2.33 eggs, the oviposition period = 13.1 ± 0.63 days). Similar with Amblyseius swirskii, the fecundity of Amblyseius swirskii in the absence of Orius sp. (the total number of eggs/females = 35.57 ± 3.62 eggs, the oviposition period = 21.33 ± 0.7 days) were higher than in the presence of Amblyseius swirskii (the total number of eggs/ females = 24.1 ± 1.67 eggs, the oviposition period = 13 ± 1.43 days). In the greenhouse with area of 300m2, the experiments were conducted when used two-predator were average aduts (Orius sp. were 3.47 adult/ leaf, A. swirskii were 6.96 adult/ leaf) were aqual as release of only Orius sp. (average adult = 3.81 adult/ leaf) or only Amblyseius swirskii (average adult = 6.49 adult/ leaf). This study also provides further evidence that intraguild predation does not necessarily have negative effects on biological control.